2007
DOI: 10.1007/s11596-007-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLR9 and its mRNA in the lesions of lichen planus

Abstract: To investigate the role of toll-like receptor 9 (TLR9) in the pathogenesis of lichen planus, the expressions of TLR9 and its mRNA in the lesional skin of lichen planus were detected by immunohistochemical technique (SP) and RT-PCR. As control, normal skin of healthy volunteers was also tested. The immunohistochemical study showed that the expression of TLR9 in the lesional skin of lichen planus was significantly higher than that in the normal controls. The results of RT-PCR showed that both skin lesions and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…Our results were in agreement with an earlier study [3], which reported upregulation of TLR9 in LP lesions. Our results were in agreement with an earlier study [3], which reported upregulation of TLR9 in LP lesions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were in agreement with an earlier study [3], which reported upregulation of TLR9 in LP lesions. Our results were in agreement with an earlier study [3], which reported upregulation of TLR9 in LP lesions.…”
Section: Discussionsupporting
confidence: 94%
“…In recent years, there has been growing interest in the role of innate immunity to explain the relation between environmental triggers and the exacerbation of autoimmune T cells leading to LP [3], with toll-like receptors (TLRs) being the link between innate and adaptive immunity [4]. TLRs have recently emerged as key sensors of invading microbes, acting through recognition of pathogen-associated molecular patterns [5].…”
Section: Resultsmentioning
confidence: 99%
“…Oral mucosa is constantly in contact with microbes that could be recognized by TLRs, and the consequent inflammation cascade could possibly play a part in the pathogenesis of oral LP (OLP). Previous studies on the expression of TLRs in LP have shown that TLR9 expression is higher in the LP skin lesions than in healthy skin (22). Enhanced expression of TLR2 in mucosal lesions as well as peripheral blood monocytes of patients with OLP was recently reported by Ohno et al.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, a recent study reported that TLR-9 mRNA was upregulated in LP, suggesting that it might play a role in the pathogenesis of the disease. 30 According to the results of this preliminary study, it seems that TLR-7 is downregulated in both HCV-positive and HCV-negative patients with LP. The reason for this downregulation may be a direct action of HCV or presence of decoy receptors in hepatic and non-hepatic patients, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, a recent study reported that TLR‐9 mRNA was upregulated in LP, suggesting that it might play a role in the pathogenesis of the disease 30 …”
Section: Discussionmentioning
confidence: 97%